Mathematical Analysis and Simulation of a Traditional Z Source Inverter using Different Control Strategies - N Bharath Kumar, P Devi Mani Deepika, Ch N Narsimha Rao, P V S Sobhan (International Journal of Advanced Science and Technology, 2020)
In recent days, Z Source Inverter (ZSI) is emerging as best alternative for conventional Voltage Source Inverter (VSI) and Current Source Inverter (CSI). This paper presents the analysis and simulation of different control strategies employed for a traditional ZSI. The most relevant control strategies and modulation techniques like Simple Boost Control (SBC), Maximum Boost Control (MBC), and Maximum Constant Boost Control (MCBC) employed for ZSI have been analyzed and simulated. Also an LC filter has been connected across the load to reduce the ripple content of the output waveform. The simulations have been carried out in MATLAB by applying a passive load to the ZSI and the results have been presented for every control strategy of the inverter. Keywords: Z Source Inverter (ZSI), Simple Boost Control (SBC), Maximum Boost Control (MBC), Maximum Constant Boost Control (MCBC), LC Filter